Even though it could be tempting to find the common denominator (60), and operate, the way the terms are ordered is inviting us to group the first and last three terms -common denominator (6 and 20 respectively)- to operate more easily:

Doing this, we can rewrite the given expression as

\(1/3 +1/2 - 5/6 + 1/5 + 1/4 - 9/20 = A + B\), where

\(A = 1/3 +1/2 - 5/6 = 2/6 + 3/6 - 5/6 = 0\)

\(B = 1/5 + 1/4 - 9/20 = 4/20 + 5/20 – 9/20 = 0\)

Thus, \(1/3 +1/2 - 5/6 + 1/5 + 1/4 - 9/20 = 0 + 0 = 0\)

Answer: A

_________________

Please, consider giving kudos if you find my answer helpful in any way

Don't worry about the world coming to an end today, it's already tomorrow in Australia